1990
DOI: 10.1016/0014-5793(90)81533-t
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NAD coenzyme on the inactivation of glyceraldehyde‐3‐phosphate dehydrogenase by anionic phospholipids

Abstract: The inactivation of bovine heart glyceraldehyde-3-phosphate dehydrogenase by phosphatidylinositol (PI) and phosphatidylserine (PS) in the form of liposomes was investigated in the presence and absence of NAD excess. In the absence of NAD, the enzyme activity decreased to about ~0% of its initial value at 0.6 mM PI and 0.8 mM PS (lipid-to-protein molar ratio 600 and 800, respectively). In the same lipid concentration range almost full regainment of the activity was observed in the presence of 80/~M NAD. It was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Sidorowicz et al [27] found that interaction of rabbit muscle GAPDH with negatively charged phospholipids decreases enzymatic activity, and that nicotinamide adenine dinucleotide could protect GAPDH from inactivation by membrane phosphatidylinositol. Glaser et al [18] proposed that a GAPDH isoform isolated from rabbit brain cytosol could mediate Ca 2ϩ -independent fusion of complex liposomes constructed to resemble a biological membrane (PC 27%, PS 6%, cholesterol 40%, and plasmenylethanolamine 27%).…”
Section: Discussionmentioning
confidence: 99%
“…Sidorowicz et al [27] found that interaction of rabbit muscle GAPDH with negatively charged phospholipids decreases enzymatic activity, and that nicotinamide adenine dinucleotide could protect GAPDH from inactivation by membrane phosphatidylinositol. Glaser et al [18] proposed that a GAPDH isoform isolated from rabbit brain cytosol could mediate Ca 2ϩ -independent fusion of complex liposomes constructed to resemble a biological membrane (PC 27%, PS 6%, cholesterol 40%, and plasmenylethanolamine 27%).…”
Section: Discussionmentioning
confidence: 99%